PENGARUH PELATIHAN, PENEMPATAN DAN KINERJA KELOMPOK PAKAR SECARA PARSIAL DAN SECARA SIMULTAN TERHADAP CAPACITY BUILDING DPRD OGAN KOMERING ILIR - Yuliana, Yuliana; Zamzam, Fakhry; Marnisah, Luis (Universitas Indo Global Mandiri Palembang, 2020)
The purpose of the research is specifically to obtain the results of the analysis of the influence of training variables, placement, expert group performance on the capacity building of DPRD partially or simultaneously. The research method uses descriptive and verification surveys, field data collection using questionnaire, interview and documentation techniques. This research is associative research, where in this study there are variables that are related and can affect other variables. The study population was 85 employees at the OKI DPRD Secretariat, taken as a sample of 71 employees. Processing data using SPSS 23 analysis tools. Testing the data using the t test, that training affects capacity building with t count 5.009> t table 1.993, there is an influence of placement on capacity building, with 3,883> t table 1,993, performance affects capacity building with t count of 2,149> t table 1,993 and training, placement and performance affect capacity building with F count 10,980> F table 2,683. The red thread of research is that Expert Group Training, Expert group Placement, Expert group performance has a positive and significant effect on the capacity building of Ogan Komering Ilir District DPRD both partially and simultaneously. Strategies to increase DPRD capacity building can be done by providing training before expert group placements on DPRD equipment.Â Keywords: training, placement, performance and capacity building